Alteration of cholesterol distribution at the plasma membrane of cancer cells: From evidence to pathophysiological implication and promising therapy strategy - Maja, Mauriane; Tyteca, Donatienne (Frontiers in Physiology, 2022)
Cholesterol-enriched domains are nowadays proposed to contribute to cancer cell proliferation, survival, death and invasion, with important implications in tumor progression. They could therefore represent promising targets for new anticancer treatment. However, although diverse strategies have been developed over the years from directly targeting cholesterol metabolism or its membrane content to adjusting sterol intake, all approaches present more or less substantial limitations related to modest efficacy, moderate-to-severe side effects, intolerance and cancer type-dependent antitumor effects. Those data emphasize the need to optimize current cholesterol targeting-based therapy protocols, to develop new specific cholesterol-targeting anticancer drugs and/or to combine them with additional strategies targeting other lipids than cholesterol. Those objectives can only be achieved if we first decipher (i) the mechanisms that govern the formation and deformation of the different types of cholesterol-enriched domains and their interplay in healthy cells; (ii) the mechanisms behind domain deregulation in cancer; (iii) the potential generalization of observations in different types of cancer; and (iv) the specificity of some alterations in cancer vs non-cancer cells as promising strategy for anticancer therapy. In this review, we will discuss the current knowledge on the homeostasis, roles and membrane distribution of cholesterol in non-tumorigenic cells. We will then integrate documented alterations of cholesterol distribution in domains at the surface of cancer cells and the mechanisms behind their contribution in cancer processes. We shall finally provide an overview on the potential strategies developed to target those cholesterol-enriched domains in cancer therapy.